The Concept of Al-Taysir al-Manhaji in DSN-MUI Fatwas: Methodological Analysis and Implications for Islamic Economics - Saputra, Edy; Hamsa, Amrizl; Sabina, Putri Alya; Muhammad, Atha Mahdi (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
This study analyzes the Al-Taysir al-Manhaji method in the issuance of fatwas by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and its implications for Islamic economic practices in Indonesia. The research aims to examine the methodology of Al-Taysir al-Manhaji, assess its relevance in Islamic economic law, and identify its impact on the implementation of Islamic financial principles. A qualitative library research method was employed, drawing on an analysis of DSN-MUI fatwas, classical and contemporary Islamic jurisprudence literature, and regulatory documents on Islamic economics. The findings indicate that the Al-Taysir al-Manhaji method facilitates flexibility in fatwa issuance while maintaining adherence to Islamic principles. This method has been applied in various DSN-MUI fatwas, including murabahah, wa’d, and Islamic hedging, supporting financial innovation and enhancing the competitiveness of Islamic banking and capital markets. The study implies that this method contributes to the harmonization of Islamic economic regulations with the national legal system. However, a robust monitoring mechanism is required to prevent the misuse of legal leniency. Future research is recommended to conduct empirical studies on the practical implementation of this method within the Islamic financial industry and comparative studies with other countries to evaluate its effectiveness in a global context.